Discrimination of hotel employees: The role of heteronormativity and political exclusion. (October 2020) - Li, Yizhi; Bogicevic, Vanja; Obeidat, Wlla E.; Bujisic, Milos
Highlights: Heteronormativity and heteronormative beliefs are introduced to the hospitality literature Diversity management theory and practice are expanded using an approach that takes into account a range of customer perceptions of diverse employees. People with strong heteronormative beliefs are more likely to discriminate against LGBTQ+ employees. Conservative people in liberal environments are more likely to discriminate against LGBTQ+ employees, however conservatives would not discriminate in conservative environments. Abstract: This study explores customers' service evaluations based on the service provided by a hotel frontline employee with different sexualities, manipulated as effeminate or masculine. Study participants were randomly assigned to respond to a video with either an effeminate or masculine hotel employee that mimics a hotel check-in experience and after are asked to evaluate check-in service. The results suggest that participants who hold stronger heteronormative beliefs are more likely to discriminate against effeminate hotel employees when evaluating the service they provided. This effect persists for the social conservatism of the participants. The study also identified a joint effect of social conservatism and political exclusion. Without tapping into sexual orientation, this study contributes to the hospitality literature by introducing sexuality and heteronormativity and adds more content to queer studies. It also suggests the need for more protection policies, management awareness, and training regarding hotel frontline employees from a diversity management perspective.